Augmented Reality (AR)-Based Learning Media on the Subject of Computer Network Installation - Mubai, Akrimullah; K, Rukun; E, Tasrif; A, Huda (Universitas Pendidikan Ganesha, 2020)
This study aims to design and build Augmented Reality (AR) - Based Learning Media on the Subject of Computer Network Installation, and analyze the validity and effectiveness of the media developed. The development model used in this study is the 4D (four-D) development model that starts from the defining, desiging, development and disseminate stages. Media validation was carried out by experts namely lecturers of the Department of Informatics Education, Department of Electronics Engineering, Faculty of Engineering, State University of Padang, who took the practical work subject of Computer Network Installation in the semester on January-June 2020. The results of this study are in the form of a blue print of media design, a job sheet book of AR-based Computer Network Installation and its application which is published on the Google Play Store under the name AR_JARKOM_INFORMATIKA-UNP. AR - Based Learning Media of Computer Network Installation is able to present practical work devices in the form of 3D virtual objects and video tutorials, so that this learning media has good mobility, independence, and interactivity in supporting independent learning. Furthermore AR - Based Learning Media on the Computer Network Installation is categorized valid from the design side with a value of 0.875 and valid from the material side with a value of 0.827. Then the use of AR-based learning media is more effective than print-based learning media based on trial data with a practical success rate of 71.79% for AR-based media and 60.92% for print-based media. So based on data from the results of this study, the learning media of AR-based Computer Network Installation is categorized as an appropriate and effective learning media to be used in practical work learning of Computer Network Installation.